2.5k views
4 votes
I need help please.

I need help please.-example-1

1 Answer

4 votes

Answer:

Explanation:

(x²-6x-3)(7x²-4x+7)= ?

Multiply each term of 2nd bracket with the 1st bracket:

=7x²(x²-6x-3) -4x(x²-6x-3) +7(x²-6x-3)

=7x^4-42x^3-21x^2-4x^3+24x^2+12x+7x^2-42x-21

Now solve the like terms:

=7x^4-46x^3+10x^2-30x-21

Therefore the answer is (x²-6x-3)(7x²-4x+7)=7x^4-46x^3+10x^2-30x-21 ....

User Ritesh  Karwa
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.